Evaluation of various toxic compounds on fungi as selction tools / Nurul Syahida Md Dauad - Md Dauad, Nurul Syahida (2009)
In this project, 24 fungi species were used in order to observe if any of them could grow in the presence of toxic compounds. Five toxic compounds were used namely benzene, ethanol, dimethyl sulfoxide (DMSO), naphthalene and 1,2-epoxybutane. A fungus is said to be resistant when it could grow in presence of toxic compounds. The objectives are; to expose a series of fungi species to five toxic compounds, to evaluate the efficiency of the toxic compounds as a selection tools and also to evaluate the metabolic changes in the surviving fungi with the presence of the toxic compound. The inoculation of fungi species into a Potato Dextrose Agar (PDA) media were conducted in a biohazard safety cabinets. The purpose of it is to prevent contamination by other microorganisms. 9cm and 20 cm of the plates were used in this project. The surviving strains then were re-cultured into 9cm plate with the presence as well as absence of the toxic compounds. These plates were incubated for two and four weeks before the extraction was done. We used HPLC as a tool to determine the presence of any new metabolites in the culture. Results showed there was several species of the fungi found to be resistant to a few of toxic compounds after it has been exposed to it. This kind of fungi may produce a secondary metabolite that was used by them to escape from being inhibited by the toxic compounds. Therefore, we have chosen benzene and naphthalene as a selection tools as it caused a relatively fungal growth with presence of it. The 1,2-epoxybutane was not chosen because it was relatively toxic to the fungi.